Lessening the Impact of Opioid Misuse at a Federally Qualified Health Center in New York: Outcomes of an Integrated Workforce Training Program. (May 2023) - Leibowitz, George S.; Turner, Win; Bruckenthal, Patricia; Mezzatesta, Maria; Ramsey, Kelly S.; Dyer, Mary Ellen
The COVID-19 pandemic has placed an unprecedented burden on patients, health care providers, and communities and has been particularly challenging for medically underserved populations impacted by the social determinants of health, as well as people with co-occurring mental health and substance use risks. This case study examines outcomes and lessons learned from a multisite low-threshold medication-assisted treatment (MAT) program at a federally qualified health center in partnership with a large suburban public university in New York to integrate and train Health Resources & Services Administration Behavioral Health Workforce Education and Training–funded graduate student trainees in social work and nursing in screening, brief intervention, and referral to treatment and patient care coordination, including social determinants of health and medical and behavioral comorbidities. The MAT program for the treatment of opioid use disorder has a low threshold for entry that is accessible and affordable, reduces barriers to care, and uses a harm reduction approach. Outcome data showed an average 70% retention rate in the MAT program and reductions in substance use. And, while more than 73% of patients reported being somewhat or definitely impacted by the pandemic, most patients endorsed the effectiveness of telemedicine and telebehavioral health, such that 86% indicated the pandemic did not affect the quality of their health care. The main implementation lessons learned were the importance of increasing the capacity of primary care and health care centers to deliver integrated care, using cross-disciplinary practicum experiences to enhance trainee competencies, and addressing the social determinants of health among populations with social vulnerabilities and chronic medical conditions.